Absence of a detectable lunar nanodust exosphere during a search with LRO's LAMP UV imaging spectrograph. Issue 10 (21st May 2017) - Grava, C.; Stubbs, T. J.; Glenar, D. A.; Retherford, K. D.; Kaufmann, D. E.
Abstract: The Lyman‐Alpha Mapping Project (LAMP) UV spectrograph on board the Lunar Reconnaissance Orbiter (LRO) performed a campaign to observe the Moon's nanodust exosphere, evidence for which was provided by the Lunar Atmosphere and Dust Environment Explorer (LADEE) Ultraviolet and Visible Spectrometer (UVS) during the 2014 Quadrantid meteoroid stream. These LADEE/UVS observations were consistent with a nanodust exosphere modulated by meteoroid impacts. LRO performed off‐nadir maneuvers around the peak of the 2016 Quadrantids, in order to reproduce, as closely as possible, the active meteoroid environment and observing geometry of LADEE/UVS. We analyzed LAMP spectra to search for sunlight backscattering from nanodust. No brightness enhancement attributable to dust, of any size, was observed. We determine an upper limit for dust column concentration of ~10 5  cm −2 for grains of radius ~25 nm, and an upper limit for dust column mass of ~10 −11  g cm −2, nearly independent of grain size for radii <100 nm. Key Points: LRO's UV spectrograph LAMP searched for the lunar nanodust cloud reported by LADEE's Ultraviolet and Visible Spectrometer (UVS) No brightness enhancement attributable to nanodust was observed during the 2016 Quadrantid meteoroid stream encounter with the Moon LRO/LAMP upper limits for line‐of‐sight nanodust concentration and mass are 2 orders of magnitude lower than those inferred by LADEE/UVS